2004
DOI: 10.1002/jsfa.1976
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of raw brown onions variably modulate plasma lipid profile and lipoprotein oxidation in pigs fed a high‐fat diet

Abstract: This study was undertaken to determine the effects of two commercially available brown onion varieties, 'Cavalier' and 'Destiny', supplemented at two different levels, on blood lipid and oxidative status using the pig as a model. Twenty-five female cross-bred pigs were allocated to one of five dietary treatments that consisted of a high-fat control diet with no onion added, a low onion dose of 10 g onion MJ −1 DE and a high dose of 25 g onion MJ −1 DE for each variety of onion. Supplementation with 'Destiny' o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 56 publications
1
19
0
2
Order By: Relevance
“…The reason for such a difference in these results is not clear at the moment, but Gabler et al have suggested that the lipid-lowering effect of onion varies with the type and dose of the onion used. 13) Few studies on the hypolipidemic activity of the Welsh onion have been reported, and this present study would be the first to propose the lipid-lowering effects of green Welsh onion in the plasma and liver of an animal model.…”
mentioning
confidence: 68%
“…The reason for such a difference in these results is not clear at the moment, but Gabler et al have suggested that the lipid-lowering effect of onion varies with the type and dose of the onion used. 13) Few studies on the hypolipidemic activity of the Welsh onion have been reported, and this present study would be the first to propose the lipid-lowering effects of green Welsh onion in the plasma and liver of an animal model.…”
mentioning
confidence: 68%
“…However, the overall fasting and postprandial plasma TG levels increased over the duration of the experiment, highlighting a period of adaptation to a high fat diet, and the greatest reductions in postprandial lipidaemia were observed in the final two weeks of the onion supplementation [3]. Since fasting concentration of plasma TG has been shown to be an important determinant of the magnitude and duration of the postprandial TG response [9], the effect of onion supplementation on fat metabolism may be more pronounced in individuals with high fasting TG levels.…”
Section: Introductionmentioning
confidence: 92%
“…The degree of oxidation of lipoproteins in diluted serum was measured according to Kontush and Beisiegel [13] as modified by Gabler et al [3]. Oxidation kinetics were determined by measuring the lipoprotein diene formation of serum exposed to Cu 2+ over a 30 h period.…”
Section: Blood Collection and Analysismentioning
confidence: 99%
See 2 more Smart Citations